THE INFLUENCE OF EWOM VIA TIKTOK APPLICATION TOWARDS PURCHASE INTENTION (STUDY ON ERIGO APPAREL IN INDONESIA) - Muhammad Dafa Bagus Efendi; Cahyaningratri Cahyaningratri (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to examine the effect of information quality, quantity, credibility, usefulness and adoption on purchase intention for the Erigo Apparel brand through the TikTok application as an electronic-word-of-mouth (eWOM) medium. Erigo Apparel is a local brand that is known to the public through social media, such as TikTok. This study aims to examine the effect of information quality, quantity, credibility, usefulness and adoption on purchase intention for the Erigo Apparel brand through the TikTok application as an electronic-word-of-mouth (eWOM) medium. This study uses the Theory Information Adoption Model (IAM) to determine the effect of TikTok as an eWOM application on increasing Erigo Aparel's purchase intention. A sample of 120 Erigo Apparel consumers in Indonesia aged 17 and up was used, with monthly spending ranging from IDR 1000,000 and up. The analytical approach is Partial Least Square Structural Equation Modeling (PLSSEM) using SmartPLS 3.0. The results of this study show that Information Quality significantly and positively affects Information Usefulness. Then, Information Quantity significantly and positively affects Information Usefulness. Moreover, Information Usefulness significantly and positively affects Information Adoption. Furthermore, Information Usefulness significantly and positively affects Information Credibility. Next, Information Adoption significantly and positively affects Purchase Intention. The last, Information Credibility insignificantly affect to Purchase Intention.